Strategic Planning of Information and Communication Technology (ICT) Sawerigading University Makassar Library - Nisa, Andi Khaerun; Ayu Trysnawati, (Literatify : Trends in Library Developments, 2022)
The Library of Sawerigading University Makassar has attempted to implement ICT to improve the services and functions, but the implementation is not optimal. In addition to the lack of human resources, libraries have to pioneer their own ICT system, so the implementation of ICT in the library is very slowly. This research uses qualitative approach. Primary data was collected through interview to the librarians, the secondary data was taken from several document sources required. Data analysis is carried out by describing and evaluating data originating from internal and external environmental factors of the library. Based on SWOT analysis results, ICT strategic planning in The Library of Sawerigading University Makassar can be divided into short and long-term strategic planning. Short-term strategic planning, i.e.: recruitment of library staff with computer science education background, improve the competence of library staff, and increase the number of ICT facilities. The long-term strategic planning, i.e.: the procurement of software and vendors, subscribe to online databases, collaboration with several libraries integrated ICT systems. Keywords: Strategic Planning; ICT; SWOT Analysis; Academic Library